The Impact of Process-oriented Guided Inquiry Learning on Students’ Academic Achievement and Capacities for Collaboration and Problem-solving - Lin , Su-Ching; Lee, Hsiao-ping (Journal of Social Science Studies, 2023)
This study investigates the impact of Process-oriented Guided Inquiry Learning (POGIL) on students’ academic performance, collaboration, and problem-solving capacities. This study adopted a two-group experimental design comprising an experimental group that received POGIL pedagogy and a control group that received traditional pedagogy. The 98 seventh-graders from a junior high school in central Taiwan comprised 51 experimental and 47 control group students. The data were collected over one semester using tests to assess academic achievement and scales to measure collaboration and problem-solving. This study used descriptive statistics: distribution frequencies, percentages, mean values, standard deviations, and inferential statistics: ANCOVA to analyze data. The results revealed that the experimental group acquired significantly higher scores on the collaboration and problem-solving scales and academic tests than the control group, indicating that POGIL pedagogy is more effective than traditional pedagogy at improving students’ academic achievement and capacities for collaboration and problem-solving. The study confirmed that POGIL pedagogy positively affected student academic achievement, collaboration, and problem-solving capacities.